On the uncertain role of agent-relativity in M. Smith’s dispositional theory of value - Parmigiani, Matías (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2022)
According to M. Smith’s dispositional theory of value, something is valuable to the extent that it would be desired by any agent who rationally deliberates from a desire set that is maximally informed, coherent, and unified. In order to assess something’s objective value, such as the value of promoting a healthy environment, for instance, the theory compels us to adopt a universal and convergent standpoint. However, what happens when we deal with acts, states of affairs or objects whose value seems to be subordinated to our actual desires, projects or personal identities? Does appreciating the value of these things also presuppose the adoption of a universal and convergent standpoint? The main objective of this paper is to determine what role personal or agent-relative values ​​play in the dispositional theory of value. Although this role will be described as ’uncertain’ or ’ambiguous’, this should not prevent us from thinking that such values ​​could find an appropriate place in this theory, alongside impersonal or agent-neutral values. To support this hypothesis, however, it will first be convenient to review some of the rationalist assumptions that Smith’s approach seems to contain.